Pentagalloyl Glucose, a Major Compound in Mango Seed Kernel, Exhibits Distinct Gastroprotective Effects in Indomethacin-Induced Gastropathy in Rats via Modulating the NO/eNOS/iNOS Signaling Pathway - Mahmoud, Mona F.; Nabil, Mohamed; Hasan, Rehab A.; El-Shazly, Assem M.; El-Ansari, Mohamed A.; Sobeh, Mansour (Frontiers in Pharmacology, 2022)
Gastric ulcers are a common health disorder that affects up to 10% of the world's population. The gastroprotective potential of pentagalloyl glucose (PGG) against indomethacin-induced ulcer in rats and the possible underlying mechanisms were investigated. Gastric ulceration was induced by indomethacin (single dose, 60 mg/kg). Pretreatment with PGG (100 or 200 mg/kg, orally), for 8 days prior to the administration of indomethacin furnished significant reductions in gastric mucosal lesions as well as a significant increase in mucus concentration. Also, PGG significantly declined the elevations in gastric mucosal MDA, TNF-α, IL-6, PECAM-1, VEGF, and iNOS expression. It also mitigated the decrease in GSH and GPx, and eNOS expression observed with indomethacin. The protective effects furnished by PGG were comparable to that of famotidine. The obtained results suggested that the anti-ulcer effects of PGG are mediated by increasing mucus production, scavenging free radicals, decreasing inflammation, and attenuating the NO/NOS signaling in favor of eNOS. To sum up, PGG could provide a potential therapy for gastric ulcer after evaluating its efficacy and effectiveness.